2019
DOI: 10.1002/mop.31942
|View full text |Cite
|
Sign up to set email alerts
|

Compact metamaterial inspired structure with bandpass characteristics for penta‐band applications using virtual ground concept

Abstract: A simple and compact metamaterial inspired filter structure for penta‐band bandpass response with minimum insertion loss is proposed in this article. The designed filter structure consists of an S‐shaped ring and two sets of meander line inductors, which provides series and shunt parallel LC circuit utilizing triangular stubs. Triangular stubs are realized as virtual grounds, which give a series combination of inductance and capacitance. A penta‐band bandpass filter operates at 1.06/1.85/2.37/2.78/3.17 GHz wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…MS is used in various frequencies for different electrical engineering fields 1 . For example, compact filters 2,3 and special antennas 4 in sub 6 GHz, reflecting focusing in K‐band, 5 flat parabolic surface for imaging, and beam propagation manipulation in W‐band 6 . MS perfect absorber was designed to detect micro‐poisons in drinking water in millimeter‐wave 7 .…”
Section: Introductionmentioning
confidence: 99%
“…MS is used in various frequencies for different electrical engineering fields 1 . For example, compact filters 2,3 and special antennas 4 in sub 6 GHz, reflecting focusing in K‐band, 5 flat parabolic surface for imaging, and beam propagation manipulation in W‐band 6 . MS perfect absorber was designed to detect micro‐poisons in drinking water in millimeter‐wave 7 .…”
Section: Introductionmentioning
confidence: 99%
“…9, it is concluded that the resonance frequency of designed bandpass filter is mainly controlled by series parameter due to shorted structure. The metamaterial properties, like complex permittivity (ε) and permeability (μ), can be evaluated using scattering parameters of D-CRLH resonator by the help of refractive index (η) and Bloch impedance (Z B ), which is calculated using scattering parameters value of D-CRLH resonator [23,24].…”
Section: Pfmentioning
confidence: 99%
“…A passband filter with quint-band response has been designed with a ring resonator, meander line and triangular stub. 18 In which two resonating modes has been achieved in each passband because of two sets of resonators. A bandpass filter with four passbands has been designed using square-ring resonators having quadruple-mode and virtual capacitive coupling structure.…”
Section: Introductionmentioning
confidence: 99%